Correlation of Carbohydrate Content with the Changes in Amylase, Invertase and ?-Galactosidase Activity of Ripe Mango Pulp During Storage under Different Temperatures (Bangladesh Journal of Scientific and Industrial Research, 2012)
Two good qualities of mango cultivars namely Fazli and Khirshapat, harvested at the full mature stage i.e. begining of ripening, have been stored at -5°C, 4°C and 25±2°C for 10 days and the changes in the content of amylase, invertase, β -galactosidase, starch, total sugar, reducing sugar and non-reducing sugar of the pulp were analyzed after 2-days regular interval of time. The activities of all the enzymes examined in the study were found to be higher in mango-pulp at 25°C as compared to those in 4°C or -5°C. The activities of amylase and invertase decreased after 8-days of storage while that of β -galactosidase increased with the increasing days of storage mango pulp. Total sugar and non-reducing sugar content of mango were increased gradually while starch content was decreased sharply with the increasing days of storage of mature mango. Changes in carbohydrate during storage of mango was found to be associated with the content of amylase, invertase and β -galactosidase. At -5°C the enzymes as well as carbohydrate content of storage mango pulp changed slightly upto 4- days and thereafter the enzyme became fully dormant. Key Words: Ripe mango; Carbohydrate; Amylase; Invertase; β -galactosidase; Temperatures DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9588 BJSIR 2011; 46(4): 443-446